Status Gizi Balita Berdasarkan Antropometri Di Tk Dm Lebak Banten Tahun 2022 - Yulica Aridawarni (Jurnal Obstretika Scientia, 2023)
The nutritional status of children under five is one of the indicators of community nutrition, and has even been developed into an indicator of community health and welfare. This is because toddlers are a group that is very vulnerable to various malnutrition diseases. Malnutrition status in toddlers based on the BB / U index showed an increase in 2018 of 10.7% (WHO, 2018) This study uses descriptive research with a cross sectional design. this study uses secondary data. The results showed the results of nutritional status research at Daaroin Maja Kindergarten Lebak Banten in 2022. From the classification found toddlers with good nutritional status 27 people 67.5%, nutritional status less 7 people 17.5%, nutritional status more as many as 6 toddlers 15%. There are several factors that influence the nutritional status of toddlers, namely the characteristics of respondents, one of which is maternal education which has a percentage. Health workers, especially midwives, should always provide information and conduct counseling to increase mothers' insight and knowledge related to balanced nutrition for toddlers and mothers always routinely follow when there is counseling.